The playful dolphins - Bridge, Linda McCarter; Georgia, Lowell ([Washington] : National Geographic Society, 1976)
Text and color photographs describe the lives of dolphins in oceanariums where some of them are trained to perform in shows.
Keywords: Dolphins -- Juvenile literature; Dolphins